Chronic Inflammation Increases the Sensitivity of Mouse Treg for TNFR2 Costimulation - Schmid, Tobias; Falter, Lena; Weber, Sabine; Müller, Nils; Molitor, Konstantin; Zeller, David; Weber-Steffens, Dorothea; Hehlgans, Thomas; Wajant, Harald; Mostböck, Sven; Männel, Daniela N. (Frontiers in Immunology, 2017)
TNF receptor type 2 (TNFR2) has gained attention as a co-stimulatory receptor for T cells and as critical factor for the development of regulatory T cells (Treg) and myeloid suppressor cells. Using the TNFR2-specific agonist TNCscTNF80, direct effects of TNFR2 activation on myeloid cells and T cells were investigated in mice. In vitro, TNCscTNF80 induced T cell proliferation in a costimulatory fashion, and also supported in vitro expansion of Treg cells. In addition, activation of TNFR2 retarded differentiation of bone marrow-derived immature myeloid cells in culture and reduced their suppressor function. In vivo application of TNCscTNF80 induced mild myelopoiesis in naïve mice without affecting the immune cell composition. Already a single application expanded Treg cells and improved suppression of CD4 T cells in mice with chronic inflammation. In contrast, multiple applications of the TNFR2 agonist were required to expand Treg cells in naïve mice. Improved suppression of T cell proliferation depended on expression of TNFR2 by T cells in mice repeatedly treated with TNCscTNF80, without a major contribution of TNFR2 on myeloid cells. Thus, TNFR2 activation on T cells in naïve mice can lead to immune suppression in vivo. These findings support the important role of TNFR2 for Treg cells in immune regulation.